2019
DOI: 10.1103/physrevx.9.031016
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Instability in Glass-Forming Mixtures

Abstract: Understanding the mechanisms by which crystal nuclei form is crucial for many phenomena such as gaining control over crystallization in glass-forming materials or accurately modeling rheological behavior of magma flows. The microscopic nature of such nuclei, however, makes their understanding extremely hard in experiments, while computer simulations have hitherto been hampered by short timescales and small system sizes. Here we use highly efficient graphics processing unit simulation techniques to address thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 52 publications
(76 reference statements)
3
53
0
Order By: Relevance
“…Previous studies observed that the crystallization of the KA system starts with the formation of pure-A nuclei [29], while in the crystallized MKA system, we also observe a pure-A crystal and an AB B2 region, as can be seen from Fig. 1(f).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Previous studies observed that the crystallization of the KA system starts with the formation of pure-A nuclei [29], while in the crystallized MKA system, we also observe a pure-A crystal and an AB B2 region, as can be seen from Fig. 1(f).…”
Section: Resultssupporting
confidence: 73%
“…S1 in the Supplemental Material [37]). In comparison, it has been shown in the literature that the nucleus in KA is in pure A [29], suggesting that the nucleation in KA is also aided by the composition change. Nevertheless, at higher B concentrations (>40%), the B2 nucleus in KA can form instead [41,42].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The value of the wave vector q is that of the first peak of the static structure factor. The 2:1 composition is a much better glass former than the standard 4:1 composition 72 74 , thus giving access to a wider dynamical range. The supercooled dynamics goes three to four decades below T MCT where the standard 4:1 composition would crystallize.…”
Section: Resultsmentioning
confidence: 99%